Etika Pergaulan Remaja di Era Media Sosial dalam Perspektif Akidah Islam Studi Kasus Kelurahan Galang Kota Kecamatan Galang - Sintia, Dona (Lembaga Yasin AlSys, 2023)
This research examines the ethics of adolescent association in the era of social media in the perspective of Islamic faith in Galang Village. The research used is a type of field research (field research) which is qualitative in the sense that the research and the author's opinion are stated explicitly in the research report. Qualitative/naturalistic research methods, carried out under natural object conditions, and research does not make treatment, because the author in this case collects emic data, namely based on the views of data sources, not the views of the author. Based on the explanation of how the impact of social media on adolescent social ethics above, the results of this research can be concluded that: as in the aspect of spirituality, social media can be a medium of information and a place for teenagers to study religion, in terms of the aspect of thinking social media can provide youth with knowledge and insight, in terms of behavioral aspects social media can be a tool in the world of communication, social media is also a lot contains content that displays examples of positive behavior and can be used as examples for teenagers.